Productivity, Business Profitability, and Consumer Surplus: Three Different Measures of Information Technology Value1,2 - Hitt, Lorin M.; Brynjolfsson, Erik (MIS Quarterly, 1996)
The business value of information technology (IT) has been debated for a number of years. While some authors have attributed large productivity improvements and substantial consumer benefits to IT, others report that IT has not had any bottom line impact on business profitability. This paper focuses on the fact that while productivity, consumer value, and business profitability are related, they are ultimately separate questions. Accordingly, the empirical results on IT value depend heavily on which question is being addressed and what data are being used. Applying methods based on economic theory, we are able to define and examine the relevant hypotheses for each of these three questions, using recent firm-level data on IT spending by 370 large firms. Our findings indicate that IT has increased productivity and created substantial value for consumers. However, we do not find evidence that these benefits have resulted in supranormal business profitability. We conclude that while modeling techniques need to be improved, these results are collectively consistent with economic theory. Thus, there is no inherent contradiction between increased productivity, increased consumer value, and unchanged business profitability.